TERRITORIAL COHESION – MAJOR DESIDERATUM OF SPATIAL PLANNING - POMPEI COCEAN; NICOLETA DAVID (Revue Roumaine de Géographie)
The concept of territorial cohesion entered recently into the scientific vocabulary, being taken over by the specialists in spatial planning, as well as the actors and stakeholders in politics and administration. It defines a fundamental feature, of structural and functional nature, belonging to the territory that aims to eliminate its dysfunctions and to make its inter-relations and productivity optimal. The inner structure of the phenomenon includes both physical features belonging to the earth, as a geographic layer and to the anthropic component, the demographic one, along with inter-relations of economic, social, political and administrative nature.